2015
DOI: 10.7860/jcdr/2015/12719.6701
|View full text |Cite
|
Sign up to set email alerts
|

Purpura Fulminans Secondary to Rickettsial Infection: A Case Report

Abstract: Purpura fulminans is an acute life threatening disorder characterized by cutaneous haemorrhagic manifestations and necrosis caused by disseminated intravascular coagulation and dermal vascular thrombosis. In this case a 60-year-old male presented with purpuric lesions over both upper and lower limbs and consumption coagulopathy following rickettsial infection. It was diagnosed as purpura fulminans secondary to rickettsial infection with disseminated intravascular coagulation and treated with replacement of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Purpura fulminans first described by Guelliot in 1884, is a heterogeneous group of disorders characterized by rapidly progressive purpuric lesions that develop into extensive areas of skin necrosis, and peripheral gangrene. 2,4 Three forms of purpura fulminans include acute infectious, neonatal and idiopathic purpura fulminans. 4 The most common form is acute infectious purpura fulminans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Purpura fulminans first described by Guelliot in 1884, is a heterogeneous group of disorders characterized by rapidly progressive purpuric lesions that develop into extensive areas of skin necrosis, and peripheral gangrene. 2,4 Three forms of purpura fulminans include acute infectious, neonatal and idiopathic purpura fulminans. 4 The most common form is acute infectious purpura fulminans.…”
Section: Discussionmentioning
confidence: 99%
“…4 Rickettsial infections have been rarely associated with purpura fulminans. 2 Pathogenesis involves activation of complement and coagulation pathways by endotoxins and signaling by inflammatory cytokines or endothelial dysfunction and vasculitis caused by the antigen. 2 Consequently there is acute transient decrease in protein C, protein S or antithrombin III levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biradar et al reported a case of a 60-year-old man who presented with purpuric lesions over both upper and lower limbs and consumption coagulopathy following rickettsial infection. He was treated with replacement of platelets and coagulation factors along with antibiotics and doxycycline, and he made an uneventful recovery [ 15 ]. Katoch et al described a case series of purpura fulminans that included four pediatric patients treated with doxycycline with good recovery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%